Evaluación de la reducción de mermas en el área de distribución sobre la rentabilidad mediante la aplicación de un software, en avícola El Rocio S.A. - Azabache Peralta, Juan Carlos (2018)
The present research work is about the implementation of a strategy that integrates each of the areas involved in the production process of El Rocio S.A. Poultry. Within the productive process the process of taking out and marketing the chickens is the last stage and it is critical and important, since many grams of live weight can be lost during the process of sacking. The investigation determined that, in the majority of poultry companies of the region do not give importance to this stage, since it is the one that causes significant losses due to the increase of the reduction. In this research, the fasting times of birds, the transport times of the birds used from the farm to the client and the reduction percentages established for each of the company's subsidiaries were evaluated. It was possible to determine that an adequate management of the entire removal process, decline control and mortality control during the distribution of live chicken; established a competitive difference. This difference was reflected in an increase in the profitability of our company. The purpose of the research was to use a software to control efficiently aforementioned indicators. Having the percentages of reduction controlled from the removal of birds from the sheds to the delivery to the customers, is a determining factor in the profitability. The reduction of the decrease obtained in the process of distribution of live chicken (for Cajamarca and Huaraz areas), with application of the software with a previously analyzed reduction factor was 1,87%. For the first year of application of the research work, the economic losses were significantly reduced, not only with the reduction of the reduction, but also with the cost of the charge (personnel, rental of collection centers).